GEOLOGICAL AND STRATIGRAPHIC STUDY OF THE MIDDLE OUERRHA, TAOUNATE (RIF, MOROCCO). - Ahmed El Bakouri1, Laila Elajhar, Douae El Khachine, Khadija El Kharrim, Mohamed Allouza4, Abdelhak Bouabdli, Jamal Chao & Driss Belghyti (International Journal of Research Science and Management, 2018)
The study area is located in the central Rif, region of the middle Ouerrha. Its bedrock is essentially composed of blue marls of the upper Tortonian, a schistose series of Cretaceous and red salt marl of the Triassic. The goal of our work will focus on the study of geological and pedological formations, as well as the study of stratigraphy, making a detailed inventory of the material reworked in it. Then establishment of structural maps of Taounate region; for a new lithological, paleogeographic and structural interpretation of the prerifainechaine. The morphostructural analysis of the study area was conducted to highlight the relationship between the basement structures and their influence in the establishment of the current tectonic structures including the reactivation of ancient faults.